Innovative care models: Expanding nurses’ and optometrists’ roles in ophthalmology - Yeo, Luke Yu Xuan (Nursing ethics, 2025)
The expanding demands of healthcare necessitate novel methods of increasing the supply of trained professionals to enhance the delivery of care services. One means of doing so is to expand allied health professionals’ scope of practice. This paper explores the ethics of two examples of such expansion in ophthalmology, comparing the widely accepted practice of nurses administering intravitreal injections and the relatively less prevalent optometrists functioning as physician extenders. We conducted a literature review of empirical research into both practices and conclude that nurses administering intravitreal injections are ethically justified. With adequate standardized training, optometrists can also function as primary eye care providers to improve accessibility to eye care. We provide an algorithm for the ethical introduction of innovative expanded allied healthcare.